Representing and Visualizing Archaeology. The Contribution of Graphic Sciences to Research in Archaeology - Enrico Cicalò; Michele Valentino (img journal)
This article discusses the role of images in archaeological disciplines and the contribution that graphic sciences can make to research in this subject area. In archaeology, and not only, ‘visualization’ differs significantly from the more commonly used noun ‘representation.’ In this sense, archaeological visualization is a practice of reconstructing and understanding the past rather than documenting and representing only the material remains that have come down to us. From archaeological drawing to virtual reality, numerous techniques and tools from the graphic sciences are applied in archaeology. Some of these can now be ascribed to the disciplinary tools, while others fall outside the specific skills of the archaeologist and require interaction with the disciplines deputed to visualization and, thus, with the graphic sciences. In order to better understand the difference between visualization and representation in archaeology, the article uses prenuragic altar of Monte d’Accoddi as a case study to focus on the creation of different graphic-visual products starting from the same model, in order to demonstrate the role of different graphic artefacts.